In vivo structure and dynamics of the SARS-CoV-2 RNA genome - Yan Zhang; Kun Huang; Dejian Xie; Jian You Lau; Wenlong Shen; Ping Li; Dong Wang; Zhong Zou; Shu Shi; Hongguang Ren; Youliang Wang; Youzhi Mao; et al. (Nature Communications, 2021)
RNA secondary structure is important for viral replication, transcription and translation. Here the authors employ SPLASH method and map in vivo RNA interactions and dynamics of SARS-CoV-2 RNA genome in different viral life cycles.